Investigating Teachers’ Language Assessment Literacy in The Implementation of the Merdeka Belajar (Freedom of Learning) Curriculum - Dinar Tyas Hutami; Nur Hidayanto Pancoro Setyo Putro (VELES Voices of English Language Education Society, 2023)
Teachers' language assessment literacy (LAL) is critical to the success of education, the quality of students' learning, and students' willingness to study. Yet, studies on teachers' LAL preparation to face the Merdeka Belajar (Freedom of Learning) curriculum are still scarce. Most LAL studies used questionnaires to assess teachers' knowledge. In contrast to that, this study utilized teachers’ LAL knowledge test adapted from Al-bahlani (2019). This study investigates teachers' self-perceived LAL consisting of competence, frequency of practice, and assessment knowledge in The Association of English Teachers Banyumas district region (MGMP) with a total of 77 participants involved by investigating teachers' self-perceived LAL consisting of competence, frequency of practice, and assessment knowledge. The current study utilized two data sources, including a questionnaire and a language assessment knowledge test to employ a quantitative methodology using MANOVA and Pearson’s product-moment correlation. The results showed both strengths and weaknesses in the teachers’ LAL, as well as matches and mismatches between teachers' self-perceived and shown assessment knowledge. Overall, EFL teachers in Banyumas regency are at a fair level of LAL and pre-service training in assessment was the variable with the greatest impact on teachers' LAL. Future research may also require investigating the objectives, actions, and outcomes of assessment training provided by teachers’ training institutes and professional development programs.  Keywords: LAL, Language assessment, Language Assessment Literacy, Merdeka Belajar curriculum, Freedom of Learning Curriculum.